The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/foods11070931
|View full text |Cite
|
Sign up to set email alerts
|

Tasting More Than Just Food: Effect of Aesthetic Appeal of Plate Patterns on Food Perception

Abstract: Interest has been growing in the role of subjective aesthetics in the field of food. This study explored the mechanisms by which the aesthetic appeal of plate patterns influences consumers’ perceptions of food. Three experiments were conducted to compare whether different levels of beauty and types of plate pattern aesthetics (classical versus expressive) affected the perceptions of tastiness and healthiness of the food offered. Experiment 1 was carried out with 30 participants, and the results showed that par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Professional photographs of the menu served in restaurants on food delivery applications significantly appeal more to consumers, and can drastically increase consumers’ purchase intentions [ 44 ]. Also, it was reported that consumers build up criteria to judge the food based on the way it is plated and presented; aesthetic dishes were believed to be more natural and healthier [ 45 , 46 ]. Despite this, participants of the present study seem to be aware that food styling can harm consumers by misleading healthiness judgments for unhealthy foods.…”
Section: Discussionmentioning
confidence: 99%
“…Professional photographs of the menu served in restaurants on food delivery applications significantly appeal more to consumers, and can drastically increase consumers’ purchase intentions [ 44 ]. Also, it was reported that consumers build up criteria to judge the food based on the way it is plated and presented; aesthetic dishes were believed to be more natural and healthier [ 45 , 46 ]. Despite this, participants of the present study seem to be aware that food styling can harm consumers by misleading healthiness judgments for unhealthy foods.…”
Section: Discussionmentioning
confidence: 99%
“…The shape of food itself, as well as the shape of the plateware on which it happens to be presented (Chen et al, 2018;Fairhurst et al, 2015;Stewart and Goss, 2013) have all been shown to bias both people's explicit taste expectations and, on occasion, also their taste experiences (Baptista et al, 2021;Wang et al, 2017a). Researchers have also investigated the impact of shapes presented on/over the plate itself (Huisman et al, 2016;Zhang et al, 2022). Researchers have suggested that staring at angular shapes can bring out the sharpness of foods such as cheddar cheese (Gal et al, 2007;Veflen et al, 2022).…”
Section: Sensory Nudging With Form -Taste Correspondencesmentioning
confidence: 99%
“…It's not always necessary to spend a lot of money and labor to present a beautiful supper. The essential components of an appealing plate presentation are ambition and creative meal planning (Zhang et al, 2022).…”
Section: Claritymentioning
confidence: 99%